LABORATORY MONITORING OF METABOLIC SAFETY DURING CARIPRAZINE TREATMENT IN SCHIZOPHRENIA AND BIPOLAR DISORDER: A SYSTEMATIC REVIEW - Kotlarska, Klaudia Magdalena; Kotlarski, Wojciech; Mainka, Tomasz; Sergejuk, Emil (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Metabolic adverse effects are a major concern during long-term antipsychotic treatment because they contribute to cardiovascular complications, endocrine disturbances, and reduced treatment adherence. Cariprazine has been considered an antipsychotic with a relatively favorable metabolic profile, but the available evidence is dispersed across studies of schizophrenia and bipolar disorder. This systematic review evaluated the laboratory-monitored metabolic safety of cariprazine in these populations.Methods: This systematic review was conducted in accordance with PRISMA 2020 guidelines. PubMed/Medline and EMBASE were searched for studies published between 2014 and 2026 using the phrase: (cariprazine OR VRAYLAR) AND (schizophrenia OR schizophreni OR "bipolar disorder" OR bipolar) AND (safety OR tolerability OR "adverse effects" OR metabol OR prolactin OR weight OR glucose OR lipid*). After screening and full-text assessment, 11 studies met the eligibility criteria and were included in the qualitative synthesis.Results: Across the included studies, cariprazine was associated mainly with modest body weight increase and limited changes in glucose- and lipid-related laboratory markers. Short-term and long-term studies in schizophrenia did not indicate a consistent pattern of clinically significant metabolic deterioration. Similar findings were reported in bipolar mania and bipolar depression. Prolactin-related data suggested minimal endocrine burden.Conclusions: Cariprazine appears to have a comparatively favorable laboratory-monitored metabolic safety profile in schizophrenia and bipolar disorder. However, regular monitoring of body weight and biochemical parameters remains necessary, and further long-term studies with standardized metabolic endpoints are needed.